The Prediction System of A Pregnant Women at Risk of Anemia Using A Fuzzy Logic - Khairul Fuady; Roza Aryani; Hayati Hayati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Prenatal development determines whether a child is normal or abnormal. The health of the mother and her nutritional intake during pre- and pregnancy will influence the birth of a healthy baby. The nutritional problems during pregnancy during antenatal check-ups are vital because nutrition is one of the factors that affect the incidence of chronic energy deficiency (CHD) in pregnant women. This research aims to prepare a prediction system for pregnant women at risk of anemia by applying fuzzy logic. This research will use steps that include problem identification, preparation of input variables , application of fuzzy logic and system testing. This research is expected to produce output variables in the form of predictions of pregnant women at risk of anemia or not at risk. The results of this study can provide valid initial information about the anemia-related conditions of a pregnant woman to avoid unwanted things during childbirth and postpartum. The rule base contains input variables (hemoglobin, blood pressure, conjunctiva examination) and output variables in the form of anemia prediction and its level in a pregnant women.